Coping Styles among Parents of Children with Autism Spectrum Disorders - Rana, Sabina; Das, Dorwin (Journal of Advanced Academic Research, 2024)
Introduction: Autism falls under the most common category of Pervasive Developmental Disorders (PDD). It is a lifelong neurodevelopmental disability characterized by persistent and pervasive impairments that include challenges with social understanding and communication, difficulty adapting to new situations, and exhibiting repetitive behaviors or interests. Caring for children diagnosed with Autism Spectrum Disorder (ASD) can be an arduous task for caregivers all around the globe. To tide through the various phases of development, certain coping mechanisms are applied by the parents of children with ASD. An impact on the level of parental distress can be evaluated being based on parental coping styles concerning developmental disabilities.Objective: To assess the coping among the parents of children with autism spectrum disorder and to measure the association of coping styles with selected background variables.Methods: A descriptive cross-sectional, questionnaire-based survey was carried out among 174 parents of children with ASD in selected autism care centers in Kathmandu, Nepal. The data was collected using a questionnaire developed by taking the reference from the Brief COPE questionnaire to evaluate the coping styles used by parents. Descriptive (mean and standard deviation) and inferential statistics (independent sample t-test) were used to analyze data in SPSS vs20.Results: The findings of the study revealed, the majority of the respondents were below 35 years of age (70.1%), female (55.2%), belonged to the Brahmin/Chhetri (63.2%) ethnic group, had a single child (62.1%), belonged to nuclear family (52.9%), were homemakers (34.5%), able to spend sufficiently economically (66.7%) and having a graduate or higher education (71.3%). Similarly, the majority of autistic children were aged between 1 to 5 years (93.1%), and were males (71.3%). In terms of birth order, the majority of children with autism were firstborns (72.4%), did not have any other illnesses (96.6%), and were diagnosed at the age of less than 3 years (62.1%). Overall, the majority of the parents used a problem-focused coping style with a mean of 3.2±0.3, followed by avoidant coping style (2.7±0.4) and emotion-focused coping style (2.5±0.5). Likewise, there was there was a significant association of avoidant coping style with the age of respondents and the number of children they have, emotion-focused coping with ethnicity, and occupation of respondents. Again, the sex of respondents, level of education of spouse, and level of autism of children of respondents were found to have a significant association with both avoidant and emotion-focused coping styles. Overall, the level of education of respondents was associated with overall coping strategies.Conclusion:  Based on the findings of the present study, the study concludes that the majority of the respondents used problem problem-focused coping style, followed by avoidant and emotion-focused coping styles. Significant associations were found between various coping styles and demographic attributes such as age, gender, ethnicity, occupation, level of education of respondents as well as their spouse, and the level of ASD of their children. Understanding the coping styles is central to supporting the parents’ coping efforts. Providing parents with effective techniques to manage their emotions can greatly influence how they view their situation, the intensity of the symptoms of their children, and the psychological distress associated with it.